Impact of Service Performance on Commuter Satisfaction in Public Transport: A Case Study of Sajha Yatayat in Kathmandu Valley - Sthapit, Arhan; Vaidya, Rashesh; B.K., Ganesh Bahadur (Kshitiz Management Review, 2025)
Public transportation is essential for urban mobility, with service performance being a key factor in customer satisfaction. Sajha Yatayat - a government-backed public transport service - has established itself as a leading provider, aimed to deliver reliable, affordable, and efficient bus services to the community. This study examines the SERVPERF dimensions of Sajha Yatayat’s services in the Kathmandu Valley, focusing on dimensions of reliability, responsiveness, assurance, tangibility, empathy, and culture. It identifies strengths and areas for improvement, providing actionable insights for enhancing service delivery and fostering a more commuter-centric public transport system. Based on the questionnaire survey successfully administered on 180 commuters sampled using a convenience sampling method, the study utilised descriptive and inferential analysis tools and concluded that reliability emerged as the key strength of Sajha Yatayat, while empathy was identified as a weakness within the SERVPERF framework among the sampled commuters. Overall, commuter satisfaction with Sajha’s services was moderately high. The findings are expected to be instrumental in providing public service management and policymakers with valuable insights to enhance service delivery systems, ensuring they better meet the needs of their target beneficiaries.